Sliding hiatus hernia (intrathoracic sleeve migration) post-laparoscopic sleeve gastrectomy: A case series and review of literature - Maher Ali Alqattan; Roshan George Varkey; Abdulmenem Abualsel (Journal of Minimal Access Surgery, 2025)
Intrathoracic sleeve migration (ITSM) is a complication that uncommonly occurs post-sleeve gastrectomy, with an incidence rate anecdotally ranging from 5% to 45%. Its treatment has established difficulties by bariatric surgeons worldwide. Sixteen cases were shown in this case series that commonly encountered the symptoms of weight gain, gastro-oesophageal reflux disease (GERD), epigastric pain, globus sensation, nausea and vomiting as their initial complaints before their diagnosis. Moreover, these symptoms began a few years after the gastric sleeve. The confirmatory results through gastrografin and computed tomography abdomen were performed where relevant findings of Grade I or II GERD, sliding hiatal hernia and post-sleeve anatomy were appreciated. In literature, the most common modality used to treat ITSM was the conversion to Roux-en-Y bypass. However, other treatment modalities were also utilised for the cases presented due to the different patients’ preferences, including mini-gastric bypass and laparoscopic hiatal hernia repair with/without posterior cruroplasty and buttress plication with the falciform ligament. In addition, anchoring to pre-pancreatic fascia post-gastric sleeve has been shown to prevent such presentations further in the future. Postoperatively, all patients were stable with no complications acutely or after 3 months follow-up. Hence, this concludes that despite Roux-en-Y being considered the golden standard treatment of ITSM, laparoscopic hiatal hernia repair with cruroplasty and plication reflects an equivalent, cost-effective and valuable alternative to treating relevant patients.